Emergence of mobilization challenger in the field: An anti-redevelopment movement of Rumah Susun Klender in East Jakarta - Galang Anugrah (Universitas Trunojoyo Madura, 2021)
This article aims to analyze the emergence of challengers of mobilization in the case of a movement against the redevelopment plan of Rumah Susun Klender in East Jakarta using a field theory approach. Mobilization issues around housing in Indonesia are not new, but it is still dominated by evictions issues. Therefore, the Rumah Susun Klender case can be considered unique. Using the case study method, data were obtained through several observation techniques, such as document study and indepth interviews with 10 informants. The results of the analysis reveal that the transformation of people resistance into the emergence of Paguyuban Tandingan (rival organization) as challenger of mobilization is not merely caused by redevelopment plans. Indeed, it was generated by an initial contention (internal dynamics) that occurred between the residents and the Association of Apartment Owners and Occupants (P3SRS). The residents who are anti-redevelopment was consolidated by, and joined with, the rival organization to take over P3SRS’ authority as a governance unit to achieve one goal: cancelling the redevelopment plan.